TINJAUAN YURIDIS TENTANG PELAYANAN ADMINISTRASI DALAM MEWUJUDKAN TERTIB PERTAHANAN DI KANTOR PERTAHANAN KABUPATEN MAROS - Fadillah Hawalia Hamzah; Ilham Abbas; Anggreany Arief (Qawanin Jurnal Ilmu Hukum, 2020)
This study aims to determine and analyse forms administrative services and realizing an orderly administrative law and affairs in the Marcs District Land Office and its factors become an obstacle in realizing an orderly land law in the office Maros Regency Land. This research was conducted by taking data from the office land of Maros Regency. Conducting interviews with employees land office and also residents of communities related to Land administration service or research is expected to be provide input fot the parties who are responsible for it Land Administration services. This research can be concluded that the implementation of service land administration in the Office in order to create order the law of Maros Fistrict shows that there is a problem with processing time that is not in accordance eith existing regulations, namely there is a delay in completing the Certificate. And the factors that are become an obstacle in realizing an orderly lan law in the office Maros Regence’s land is domething people want to submitted a request for issuance of the file rights certificate has not complete and the right applicant could not be contacted or the applicant and suggested to the Maros Regency Government, government officials at The Maros Regency Land Office was given the oppoetunity to Participate education and training, both technical and non-technical with hope, the creation of a skilled and friendly workforce.